(untitled) (Altre Modernità, 2020)
This article explores the notions of flotsam, jetsam and hybridity in John Keats’s poetry in order to provide a critical reading informed by posthumanist theories, and, more specifically, Donna Haraway’s cyborg. It starts with the metaphor of debris and the linguistic-literary metaphor of texture/textus. It then proceeds to elucidate how Keats deals with flotsam and jetsam in his work. A short overview of the theory of organic unity begins the last section of the article, which focuses on the poet’s penchant for hybrid poetic endeavours and envisions some of his work as a metaphorical manifestation of the cyborg myth.